2018
DOI: 10.1002/chem.201802799
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence from Lanthanide(III) Ions Bound to the Glycocalyx of Chinese Hamster Ovary Cells

Abstract: Lanthanide(III) ions bind to the glycocalyx of Chinese Hamster Ovary (CHO) cells and give rise to a unique luminescent fingerprint. Following direct excitation of terbium(III) and europium(III) ions in the visible part of the spectrum, we are able to collect emission spectra pixel-by-pixel in images of CHO cells. Following data analysis that removes the background signal, the fine structure of the europium(III) luminescence indicate that the lanthanide(III) ions are bound to a single structure of the CHO cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Control of the spectroscopic and chemical properties at the molecular level and the higher cell penetrability, due to the small size, of Ln III luminescent complexes, are advantages for use in luminescence imaging of biological systems. The formation of the Ln III complexes inside the cells is the most straightforward strategy used in luminescence imaging [117,118]. For example, treatment of Hepg2 cells with Eu(NO 3 ) 3 produced a luminescent Eu III complex that is not observed using the healthy L02 cell lines [117].…”
Section: Visible Emitting Ln III Complexes In Bioimagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Control of the spectroscopic and chemical properties at the molecular level and the higher cell penetrability, due to the small size, of Ln III luminescent complexes, are advantages for use in luminescence imaging of biological systems. The formation of the Ln III complexes inside the cells is the most straightforward strategy used in luminescence imaging [117,118]. For example, treatment of Hepg2 cells with Eu(NO 3 ) 3 produced a luminescent Eu III complex that is not observed using the healthy L02 cell lines [117].…”
Section: Visible Emitting Ln III Complexes In Bioimagingmentioning
confidence: 99%
“…Although there is selectivity towards cancer cells, the identity of the ligands bonded to Eu III could not be figured out, and only a possible mechanism of formation involving NADPH was proposed. Attempts to get more information about the identity of the complexes formed in CHO cells treated with Eu III or Tb III acetate were made by Sørensen and co-workers, using a state-of-the-art confocal microscope [118]. The comparable intensities of the 5 D 0 → 7 F 1 and 5 D 0 → 7 F 2 transitions in the emission spectra suggested that the Eu III is in a high symmetry coordination environment [118].…”
Section: Visible Emitting Ln III Complexes In Bioimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordination of the luminescent lanthanide ion inside supramolecular chelates or cryptates can enhance the absorption by more than 1000-fold via the antenna effect and efficiently protect the lanthanide ion from the environment to circumvent PL quenching and yield high PL quantum yields [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Such bright and stable lanthanide complexes have been used in many different applications concerning highly sensitive, multiplexed, and background-free biological and chemical sensing and imaging [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…By combining fluorescence methods with microscopy, one can obtain diffraction limited spatial information, which allows probing heterogeneities of micro-and nanostructures. One of such approaches involves measuring spatially resolved spectral information [3][4][5]. This so called hyperspectral imaging approach has promoted fundamental progress for the investigation of various samples e.g.…”
Section: Introductionmentioning
confidence: 99%